Research in personnel and human resources management. Vol. 24 - Martocchio, Joseph J. (Emerald, 2005)
This series publishes monograph length conceptual papers designed to promote theory and research on important substantive and methodological topics in the field of human resources management. Volume 24 of "Research in Personnel and Human Resources Management" (RPHRM) contains seven papers on critical issues in the field of human resources management, thus continuing the tradition of the series to develop a more informed understanding of the field. The papers include: A Multi-Level Application of Learning and Performance Orientations to Individual, Group, and Organizational Outcomes; Justice in Teams: A Review of Fairness Effects in Collective Contexts; Standing Up or Standing By: What Predicts Blowing the Whistle on Organizational Wrongdoing?; A Model of Employee Self-Service Technology Acceptance; Learner Control and Workplace E-Learning: Design, Person, and Organizational Issues; Goal Propensity: Understanding and Predicting Individual Differences in Motivation; and, "The Elusive Criterion of Fit" Revisited: Toward an Integration Theory of Multidimensional Fit.
Keywords: Personnel management.; elektronické knihy; electronic books